USE OF THE LATEST INFORMATION TECHNOLOGIES, ACHIEVEMENTS OF SCIENTIFIC AND TECHNICAL DEVELOPMENT IN THE PROCESS OF STUDYING THE SCIENCE OF DESCRIPTIVE GEOMETRY AND COMPUTER GRAPHICS - M.Х.Imomov (Scientific Impulse, 2024)
This article discusses the use of modern information technology in the teaching of descriptive geometry and engineering. In addition, there are conveniences for students studying in technical areas to work in computer programs AutoCAD and 3D MAX.